EDUCATION AND ASSESSMENT OF LEARNING OUTCOMES IN LITHUANIAN SPECIAL SCHOOLS - Kaffemaniene, Irena; Meliene, Rita; Milteniene, Lina; Geleziniene, Renata; Kairiene, Daiva; Tomeniene, Laima (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The strategic aims of Lithuanian education orientate towards the development of inclusive education. However, in addition to mainstream schools, special schools still exist as well. In this context, future perspectives of special schools and their role in the inclusive education system has become a particularly relevant problem; therefore, it is important to analyse experiences of education in special schools.The aim of the study presented in the article is to analyse teachers’ opinion regarding special education and assessment of outcomes. The study was conducted in special schools of Lithuania, using a questionnaire method. Based on the data of the analysis of scientific literature sources, the ranking scale of variables (statements describing various dimensions of education and assessment of outcomes) was drawn up (respondents marked answers from 1 – strongly disagree to 5 – strongly agree).The results of the study show that teachers of special schools understand priorities of contemporary education. This is demonstrated by strong approval of statements about fostering of self-esteem, development of communication and problem-solving abilities of special school students; search for non-traditional forms of education; involvement of school community in education. Nevertheless, in the opinion of a considerable share of special school teachers, individual teaching and a traditional lesson are more effective compared with the variety of learning methods. In the opinion of many special school teachers, the purpose of special education is to cope with students’ disorders, and only specialized educational institutions can ensure quality individualised education. Respondents also noted certain shortcomings of education at special schools.